High Magnetic Transition Temperature and Semiconductor like Transport Properties of Mn-doped α-YbAlB4. (January 2016) - Suzuki, S; Tomita, T; Shimura, Y; Kuga, K; Matsumoto, Y; Nakatsuji, S
Abstract: We succeeded in growing single crystals of α-YbAl1– x Mn x B4 by the substitution of Mn for the Al site in the intermediate-valence rare-earth heavy fermion system α-YbAlB4 . We performed specific heat and resistivity measurement on single crystals of α-YbAl1– x Mn x B4 ( x = 40). In the specific heat measurement on α-YbAl0.60 Mn0.40 B4, a sharp peak was observed at magnetic transition temperature T M = 9.7(6) K. The resistivity measurements on x = 0.40 also show a semiconductor-like behavior in the entire temperature range from 2 - 300 K. An inclination change was also observed at 10(1) K in resistivity measurement. These results indicate a magnetic order. The magnetic transition temperature is quite high compared to its temperatures observed in the other Yb-based heavy fermion compounds.